The Solid Waste Management System and Its Impact on the Sustainable Development of the Resort Area. A Case from Kazakhstan - BESPALYY, Sergey (Journal of Environmental Management and Tourism; Vol 13 No 5 (2022): JEMT, Volume XIII, Issue 5(61), Fall 2022DO - 10.14505/jemt.v13.5(61).02, 2022)
The article examines the current management system for heavy household waste (MSW) in resort areas in Kazakhstan. The work carried out an assessment of the municipal solid waste management infrastructure, which used the data of experts in the field of sustainable development in terms of environmental impact. The analysis of the prerequisites for the creation of a solid waste management system in the Shortandy-Burabay and Bayanaul resort zones has been carried out. Analysis of the dynamics of production and consumption waste generation shows a sharp tendency for their increase in recent years in the areas of resort areas. This is mainly due to the improvement in the general economic situation. The sanitary situation in resort areas is significantly complicated by environmental pollution by waste from settlements, recreational complexes, industrial and agricultural enterprises. Waste from production and consumption is stored in certain places, the organization and content of which in most cases does not meet regulatory requirements. The article proposes an integrated solid waste management system. The introduction of an integrated management system will reduce the volume of waste disposal, as well as bring economic and social effects in the considered resort areas.